Pengaruh Kualitas Layanan, Servicescape Dan Kepercayaan Terhadap Kepuasan Pelanggan Pada Rumah Cantik OASIS DEYNE - Meri Emilda (JURNAL PUNDI, 2021)
Fast traslate Icon translate     Fast traslate Icon translate Every company will always try to always maintain customer satisfaction. Because at this time that the main key to winning a competition is to provide value and satisfaction to customers through the delivery of quality products and services at competitive prices. This customer satisfaction is determined by the quality of service, servicescape and trust gained by the customer.The purpose of this study was to determine the Effect of Service Quality, Servicescape and Trust on Customer Satisfaction at the Oasis Deyne Beauty House, based on the results of tests that have been done can be known 1. Tangible affects customer satisfaction, where it can be seen from the value of t-count more big of t-table value with small sign value of alpha value. 2. Empathy effect on customer satisfaction, where it can be seen from the t-value greater than the t-table value with a small sign value than the alpha value. 3. Reability does not affect customer satisfaction, where it can be seen from the t-count value is smaller than the t-table value with a large sign value from the alpha value. 4. Responsiveness has no effect on customer satisfaction, where it can be seen from the t-count value is smaller than the t-table value with a large sign value from the alpha value. 5. Servicsscape influences customer satisfaction, where it can be seen from the t-value greater than the t-table value with a small sign value from the alpha value. 6. Trust affects customer satisfaction, where it can be seen from the t-value greater than the t-table value with a small sign value from the alpha value.